Frequency of Risk Factors for Developmental Dysplasia of the Hip in Patients Presenting to a Tertiary Care Hospital: Risk Factors for Developmental Dysplasia of the Hip - Saqib, Muhammad; Saud, Abdul Munaf; Kakar, Aman Ullah Khan; Abidi, Syed Abdur Rub; Saleem, Muhammad Shoaib; Ullah, Zia; Khan, Amina Gul Shehzar (Pakistan Journal of Health Sciences, 2025)
Developmental dysplasia of the hip (DDH) involves abnormal hip joint development and is influenced by several perinatal risk factors. Early diagnosis is essential for optimal management. Objective: To evaluate the frequency of DDH-associated risk factors and their statistical associations. Methods: A cross-sectional study was conducted at Quaid-E-Azam Medical College, Bahawalpur, from January to August 2024. A total of 153 DDH patients were included. Risk factors such as gender, gestational age, birth weight, mode of delivery, breech presentation, oligohydramnios, multiple pregnancies, firstborn status, family history, and maternal complications were documented. Associations were analyzed using chi-square tests (p<0.05). Results: Of the 153 patients, 77 (50.3%) were male and 76 (49.7%) female. Term births were predominant (75.2%), and 19.6% had low birth weight. Breech presentation was seen in 13.7%, and oligohydramnios in 16.3%. Cesarean section accounted for 66.7% of deliveries, with no significant association with breech presentation (p=1.000). A significant association was found between multiple pregnancies and low birth weight, as all multiple births had low birth weight infants (p=0.000). No significant associations were found for gender, oligohydramnios, firstborn status, or family history. Conclusions: It was concluded that multiple pregnancies and resulting low birth weight showed a significant association with DDH. Other risk factors, including breech presentation and oligohydramnios, demonstrated no significant correlation. Focused DDH screening is recommended in infants from multiple gestations with low birth weight to ensure early detection and intervention.